Socioeconomic Conditions Along the Community in Kampar Watershed Kecamatan Pelalawan Kabupaten Pelalawan - Ayu, Fitri; Juita, Erna; Nefilinda, Nefilinda (Pendidikan Geografi, 2013)
River Watershed (DAS) is an area of land that is bounded by the topographic ridges that hold and store rainwater for later channeled to the sea through the main river. Function of a river basin (DAS) is a combined function performed by all the factors that exist in the watershed such as social factors also have an important role to other forms of use of the environment as a source of livelihood such as farming places, residences, estates and fishery. The purpose of this research is to getÂ  data, process, analyze and discuss the socio-economic Conditions along the Kampar river basin district Pelalawan PelalawanThis type of research is descriptive. The population sample consists of 1794 respondents KK. and using proportional random sampling technique. Sample size was 90 households. Instrument used in this study is a questionnaire or a questionnaire. Data analysis using the percentage formula.Results of this study found: 1) the livelihoods of the communities along the watershed Kampar District Pelalawan quite varied but the most widely farmed 50%. 2) The level of income of the people along the river basin Pelalawan Kampar district average of USD 500-000 thousand to 1 million rupiah, sideline USD 500,000 thousand to 1 million and expenditures of Rp 1 million to 2 million dollars 3) The level of public education in all areas District of Kampar river Pelalawan the most complete primary school and 28.9% had not completed at least 1.1% PT. 4) interaction of the communities along the watershed Kampar District Pelalawan in the left and right most watershed Kampar 77.8% and 6.7% both at least poorly.